THE IMPACT OF SOCIAL MEDIA ON TEEN HEALTH IN THE DIGITAL ERA HINAI KIRI - Nura’ini, Nura’ini; Haikal, Muhammad Fachran (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study aims to analyze the impact of social media on adolescent health in Hinai Kiri Village by highlighting subjective experiences, behavioral patterns, and the resulting social consequences. The research employs a qualitative approach with a case study design, involving adolescents aged 13–18 years as primary informants, as well as teachers, parents, and community leaders as supporting informants. Data were collected through in-depth interviews, participant observation, and documentation, and were analyzed using thematic analysis to identify patterns and themes related to the effects of social media on adolescent health. The findings indicate that intensive use of social media, particularly platforms such as TikTok and Instagram, has a significant impact on mental health, manifested in social anxiety, sleep disturbances, and low self-esteem due to social comparison. In terms of physical health, symptoms such as eye strain, neck pain, and sedentary lifestyles were identified as consequences of excessive gadget use. Meanwhile, in the social dimension, there has been a shift from direct face-to-face interaction to shallow virtual communication, which reduces adolescents’ ability to empathize and engage in meaningful interpersonal interactions